DINAMIKA PENAFSIRAN AL-QURAN DI SURAKARTA: 1900-1930 - Junaidi, Akhmad Arif (Universitas Muhammadiyah Surakarta, 2013)
The interpretation dynamics of Al-Quran was so intensive in Surakartawithin 1900-1930. By comparative analysis this paper studies and finds three works oftafsir (interpretation, exclamation passage of al-Qu?ran by supplying additionalinformation) that were published in Surakarta but they had different concern. Tafsîral-Quran al-?A?îm analyzed Islamic orthodox theme as the central issue in itsinterpretation. This can be understood because the work was written by a Great SurakartaPalace village leader who splashed around Islamic laws. While Tafsir Surat Wal-Asridiscussed the relation between Islam and Christianity as the central issue. The writer ofthis book was worried about the activity of the evangelism in the Surakarta Palaceterritory. Tafsir Qur?an Djawen stressed on the importance of the fraternity as thecentral issue in its interpretation. The book talked about the disunity phenomena amongMuslim community because of the difference in the furu?iyah cases.Key Words: interpretation dynamics, al-Quran, SurakartaDinamika penafsiran al-Quran begitu intens di Surakarta dalam rentangwaktu antara 1900-1930. Dengan analisis perbandingan makalah ini mengkaji danmenemukan tiga karya tafsir yang sama-sama diproduksi Surakarta memiliki concernyang berbeda. Tafsîr al-Quran al-?A?îm lebih banyak menjadikan tema ortodoksi Islamsebagai isu sentral dari penafsiran-penafsirannya.Hal ini tentu bisa dimengerti karenakarya tafsir tersebut ditulis oleh seorang pengulu agengkraton yang banyak bergelutdengan hukum Islam.Sedangkan Tafsîr Surat Wal Acri lebih banyak menjadikan temahubungan Islam-Kristen sebagai isu sentralnya.Penulis kitab ini tampak dirisaukanoleh kegiatan-kegiatan zending yang semakin meraja-lela di kawasan KasunananSurakarta. Kitab Tafsîr Qur?an Djawen menjadikan pentingnya ukhuwwah Islamiyyahsebagai isu utama penafsiran-penafsirannya. Dalam kitab ini tampak banyak diuaraikanfenomena perpecahan di kalangan umat Islam dikarenakan perbedaan-perbedaan dalammasalah-masalah furu?iyyah.Kata Kunci: Dinamika Penafsiran, Al-Quran, Surakarta